Emission Characteristics of Lasing From all Organic Mirrorless Quasicrystal - Zongdai Liu; Dan Luo; Qingguo Du; Yong Li; Haitao Dai (IEEE Photonics Journal, 2016)
We demonstrate the emission characteristics, including polarization property and temperature effect, of lasing from all organic mirrorless quasicrystal fabricated by seven-beam interference. The output lasing is linearly polarized with polarization direction confined within the 2-D plate that aperiodic quasicrystal formed. With an increase of temperature, lasing peaks blue-shift that is related to the change of refractive index of liquid crystal, as well as phase transition from liquid crystal phase to isotropic phase. The transmission spectrum of quasicrystal that is calculated by finite-difference time-domain (FDTD) simulation blue shifts with the increased temperature, which can be used to explain the underlying mechanism of the blue-shift of lasing peaks.